Molecular magnetic resonance imaging of atherosclerotic vessel wall disease - Noerenberg, Dominik; Ebersberger, Hans U.; Diederichs, Gerd; Hamm, Bernd; Botnar, Rene M.; Makowski, Marcus R. (European Radiology, 2016)
Abstract: Molecular imaging aims to improve the identification and characterization of pathological processes in vivo by visualizing the underlying biological mechanisms. Molecular imaging techniques are increasingly used to assess vascular inflammation, remodeling, cell migration, angioneogenesis and apoptosis. In cardiovascular diseases, molecular magnetic resonance imaging (MRI) offers new insights into the in vivo biology of pathological vessel wall processes of the coronary and carotid arteries and the aorta. This includes detection of early vascular changes preceding plaque development, visualization of unstable plaques and assessment of response to therapy. The current review focuses on recent developments in the field of molecular MRI to characterise different stages of atherosclerotic vessel wall disease. A variety of molecular MR-probes have been developed to improve the non-invasive detection and characterization of atherosclerotic plaques. Specifically targeted molecular probes allow for the visualization of key biological steps in the cascade leading to the development of arterial vessel wall lesions. Early detection of processes which lead to the development of atherosclerosis and the identification of vulnerable atherosclerotic plaques may enable the early assessment of response to therapy, improve therapy planning, foster the prevention of cardiovascular events and may open the door for the development of patient-specific treatment strategies. Key Points: • Targeted MR-probes allow the characterization of atherosclerosis on a molecular level. • Molecular MRI can identify in vivo markers for the differentiation of stable and unstable plaques. • Visualization of early molecular changes has the potential to improve patient-individualized risk-assessment.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Atherosclerotic vessel wall disease; Cardiovascular disease; Magnetic resonance imaging; Molecular imaging; MRI contrast agents